2017
DOI: 10.1021/acs.estlett.7b00124
|View full text |Cite
|
Sign up to set email alerts
|

Active Tetrahedral Iron Sites of γ-Fe2O3 Catalyzing NO Reduction by NH3

Abstract: Maghemite (γ-Fe 2 O 3 ) with a spinel structure, consisting of tetrahedral Fe 3+ (Fe 3+ Td ) and octahedral Fe 3+ (Fe 3+ Oh ) sites, has been intensively investigated as an environmentally benign catalyst for selective catalytic reduction (SCR) of NO x with NH 3 . In most cases, Fe 3+ Oh sites were regarded as catalytically active sites (CASs). Here we identify the CASs in SCR by substituting Fe 3+ Oh or Fe 3+ Td sites of γ-Fe 2 O 3 with catalytically inactive Ti 4+ or Zn 2+ , respectively. The SCR activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 30 publications
(65 reference statements)
3
41
0
Order By: Relevance
“…Therefore, the combination of the above structure characterizations and the SCR activity and stability tests demonstrate that the site‐specific Ti 4+ doping significantly improves not only the thermal stability of γ‐Fe 2 O 3 , but also the catalytic performance in SCR. As reported in our recent work, Fe 3+ Td sites serve as catalytically active sites in SCR due to much easier electron transfer from inactive Fe 2+ to active Fe 3+ in the tetrahedral site than that in the octahedral site. In fact, lattice oxygen species also play an important role in SCR, especially in activating NH 3 molecules .…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Therefore, the combination of the above structure characterizations and the SCR activity and stability tests demonstrate that the site‐specific Ti 4+ doping significantly improves not only the thermal stability of γ‐Fe 2 O 3 , but also the catalytic performance in SCR. As reported in our recent work, Fe 3+ Td sites serve as catalytically active sites in SCR due to much easier electron transfer from inactive Fe 2+ to active Fe 3+ in the tetrahedral site than that in the octahedral site. In fact, lattice oxygen species also play an important role in SCR, especially in activating NH 3 molecules .…”
Section: Resultssupporting
confidence: 67%
“…As shown in the SXRD patterns of the samples calcined at 400 °C instatic air (Figure S2), the spinel structure of Ti‐γ‐Fe 2 O 3 remains, whereas γ‐Fe 2 O 3 has been transformed to α‐Fe 2 O 3 with a more stable hexagonal structure, thus leading to a partial loss of catalytic activity at low reaction temperatures (Figure S3). Besides, our recent work showed that Ti‐γ‐Fe 2 O 3 exhibited slightly better SCR performance than γ‐Fe 2 O 3 at a relatively low gaseous hourly space velocity (GHSV) of 300,000 h −1 . In order to clearly distinguish the differences of the stabilities and activities of Ti‐γ‐Fe 2 O 3 from γ‐Fe 2 O 3 , the catalysts were tested under a more demanding condition, i.e., at a high GHSV of 600,000 h −1 in the presence of H 2 O and SO 2 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To elucidate the role of the spinel structure in NiFe 2 O 4 , the structure–activity relationship among iron oxides needs to be understood. The structure‐dependent activity of iron oxide has been studied for other reactions . Although it was concluded that acid–base or redox properties were important factors for the catalytic activity, the impact of the difference in circumstances around iron has not been discussed in depth.…”
Section: Introductionmentioning
confidence: 99%